2013
DOI: 10.5216/ree.v15i1.16643
|View full text |Cite
|
Sign up to set email alerts
|

Características sociodemográficas e hábitos de vida de idosos com e sem indicativo de depressão

Abstract: Objetivou-se comparar as variáveis sociodemográficas e hábitos de vida dos idosos com e sem indicativo de depressão. Trata-sede um inquérito domiciliar, descritivo, transversal e observacional, do qual participaram 850 idosos residentes na zona rural de um município de Minas Gerais. Utilizaram-se os instrumentos estruturados e a Escala de Depressão Geriátrica Abreviada, seguidos de análise descritiva e teste qui-quadrado (p<0,05). Predominaram os idosos com indicativo de depressão do sexo feminino, 80 anos ou … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
1
11
1
3
Order By: Relevance
“…20 While common in all stages of life, it is more prevalent among the elderly than in younger people. Furthermore, approximately 40% of cases of depression in old age are not diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…20 While common in all stages of life, it is more prevalent among the elderly than in younger people. Furthermore, approximately 40% of cases of depression in old age are not diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Faced with this problem, there is in Primary Health Care (PHC) the unpreparedness of some professionals in dealing with this disorder that cycle of life, which confirms low rates of identification and treatment of depression at this level of attention [1]. Study indicates that the PHC of services are important spaces for screening depressive symptoms by applying the short Geriatric depression Scale (GdS) at the time of nursing consultation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the presence of depression among the elderly is one factor that is associated with suicidal ideation and suicide attempt, and consequently, with the act of suicide. 1,2 Studies profiling elderly individuals who have attempted suicide are necessary for developing preventive care plans for this vulnerable group. In addition, the education of primary care providers in diagnosing and treating depression is an evidence-based suicide prevention practice.…”
Section: ' Introductionmentioning
confidence: 99%
“…3 When undiagnosed and untreated, depression -a common psychiatric disease among the elderly 4 -can cause physical, social and functional impairment, thereby contributing to decreased quality of life and, at more severe degrees, to suicide. 1 Suicide among the elderly is a global public health problem that is expected to worsen as society ages. 5 Consequently, health professionals must be attentive to the signs and symptoms of depression and the risk factors that can trigger depression.…”
Section: ' Introductionmentioning
confidence: 99%